2024
DOI: 10.1038/s41746-024-01076-x
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking clinical trials with synthetic acute myeloid leukemia patients using generative artificial intelligence

Jan-Niklas Eckardt,
Waldemar Hahn,
Christoph Röllig
et al.

Abstract: Clinical research relies on high-quality patient data, however, obtaining big data sets is costly and access to existing data is often hindered by privacy and regulatory concerns. Synthetic data generation holds the promise of effectively bypassing these boundaries allowing for simplified data accessibility and the prospect of synthetic control cohorts. We employed two different methodologies of generative artificial intelligence – CTAB-GAN+ and normalizing flows (NFlow) – to synthesize patient data derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The second approach to developing in silico clinical trials is to retrospectively use big data and artificial intelligence algorithms to identify patients eligible for clinical trials and achieving this by aggregating and structuring data from patients' medical records [20,21]. A concrete illustration of this strategy comes from the study by Eckardt and coworkers [22]. The authors demonstrated the feasibility of two different technologies of generative AI to develop synthetic clinical trial data for patients with acute myeloid leukemia and that closely mimic disease biology and clinical behaviors.…”
Section: In Silico Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second approach to developing in silico clinical trials is to retrospectively use big data and artificial intelligence algorithms to identify patients eligible for clinical trials and achieving this by aggregating and structuring data from patients' medical records [20,21]. A concrete illustration of this strategy comes from the study by Eckardt and coworkers [22]. The authors demonstrated the feasibility of two different technologies of generative AI to develop synthetic clinical trial data for patients with acute myeloid leukemia and that closely mimic disease biology and clinical behaviors.…”
Section: In Silico Clinical Trialsmentioning
confidence: 99%
“…Additionally, machine learning models reach a high level of complexity and may constitute impenetrable "black boxes" with the output difficult to interpret. There is also a risk for an unavoidable widening gap between how fast technologies like AI are devised and how quickly regulatory agencies may establish legal rules for safe implementation [22].…”
Section: Critical Appraisal (Table 1)mentioning
confidence: 99%